From evaluation to auditing and from programs to institutions: Causes and consequences of the decline of the program approach. Issue 3 (8th May 2020) - Peters, B. Guy; Pierre, Jon
Abstract: In the wake of the "audit revolution" during the 1980s and 1990s, administrative systems across the western world have tended to gradually downplay evaluation as a component of the policy process. At the same time, auditing has dramatically increased in scope and depth, and has also, to some extent, come to fill the role in policymaking previously played by evaluation studies. This article reviews this development from the perspective of policymaking and institutional change or "drift." Specifically, we look at the types of information and knowledge that are lost and gained as a result of these developments. We apply a cross‐national approach, drawing on the examples from the European and North American contexts.